Factors that Influence Business Success - Addinil Gunawan (Journal of Islamic Economic Scholar, 2021)
Business today seems to be something that must be owned by someone. Because in business we can arrange for themselves what is in it, unlike the case with work or become employees with many attachments in it. In running a business, it is very necessary for a leader who is wise in making decisions and can arrange for his subordinates to be able to bring the company led to success. A leader must be able to solve every problem that threatens the company. Various attempts were made so that the problem can be solved appropriately without bringing negative influence. Someone who founded a business must have an initial goal to be achieved, because with the goals can increase the enthusiasm for leaders and subordinates in achieving that goal so they will always work hard to achieve that goal. This discussion is intended to broaden the reader's insight so that he can run his business, especially in dealing with various obstacles or problems that come. This study uses the literature review method which requires some literature derived from journals as a reference. This research shows that there are many success factors in doing business, not just mere activities, but there are others that are important to know.